Diversity and the sense of heritage: a contribuition based on the anthropological perspective on territory for the study of traditional communities (Terr@ Plural, 2011)
When investigating socio-environmental complexities, it seems important to develop and test theoretical-methodological strategies that allow for local investigations without disregarding linkages to global aspects. This research is an attempt to contribute, from an anthropological perspective on the territory, to the study of local territorial processes in which local communities are involved. Therefore, its main objective is to add to the interdisciplinary study of traditional communities highlighting especially the following aspects: a) the need to investigate the internal differences in traditional communities, b) the need to re-evaluate the knowledge and traditional wisdom of different actors based on the concept of the “sense of heritage”. Thus, an attempt is made to regain a new enchantment of the world to “construct our future”.